Prevalence of anaemia in children newly registered at UNRWA schools: a cross-sectional study. (March 2019) - Abu Kishk, Nada; Hababeh, Majed; Saleh, Suha; Turki, Yassir; el Khiteb, Zohair; Kassim, Nimer; Arab, Hasan; Zeidan, Wafaa; Seita, Akihiro
Abstract: Background: Children entering first grade at United Nations Relief and Works Agency for Palestine Refugees in the Near East (UNRWA) schools across the five fields of its operations (West Bank, Gaza, Lebanon, Jordan, and Syria) complete a comprehensive medical examination at UNRWA health centres as a requirement for their acceptance. Our study aimed to assess the prevalence of anaemia and undernutrition indicators in these children. Methods: We conducted a cross-sectional study at 59 UNRWA health centres, targeting all children entering grade one at UNRWA schools in Gaza, West Bank, Syria, and Lebanon in 2017. The children included boys and girls living inside and outside Palestine refugee camps. Using Epi-Info V2000, a weighted sample of 2399 was calculated (Gaza, 961; West Bank, 982; Syria, 334; Lebanon, 622) based on the prevalence of anaemia in a previous study (2005) and the total number of first grade students at UNRWA schools during the school year 2016–2017, with a confidence level of 95% and precision of 3%. Descriptive statistics were obtained and chi squared tests were carried out using SPSS v22. Child growth z-scores were calculated using WHO Anthroplus software. Informed verbal consent was obtained from parents. Findings: 2419 students (1278 females and 1141 males) aged 6·1 (SD 0·4) years were examined. The prevalence of anaemia (haemoglobin level of <11·5 mg/dL) was 25·0% (Gaza, 29·3%; West Bank, 22·0%; Syria, 30·0%; and Lebanon, 18·3%) with no significant differences between males and females (p=0·383). The mean haemoglobin level was 12·0 [SD 0·9] mg/dL. Stunting, underweight, and thinness were assessed according to WHO growth indicators. The overall prevalence of stunting, underweight, and thinness were 3·2%, 3·5%, and 5·6%, respectively, with the highest levels found in Syria (4·3%, 6·3%, and 10·1%, respectively). Interpretation: The overall prevalence of anaemia in surveyed children (25·0%) was higher than in the 2005 study (19·5%). However, the prevalence in children in Gaza (29·3%) was lower than in 2005 (36·4%). Haemoglobin testing should be included as part of the medical examination for new school children. In addition, malnutrition among these children should be investigated further. Funding: Health Programme at UNRWA Headquarters, Amman, Jordan.